Diaphragm and preparation method thereof, battery and electric device

CN119585935APending Publication Date: 2025-03-07CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202380051157.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-01-06
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

When existing safety-modified separators improve the safety of thermal runaway of batteries, they reduce the wettability of the electrolyte, resulting in a decrease in the electrochemical performance of the battery.

Method used

An organic particle coating is placed on the base film. By controlling the particle size and non-ionic group content of the organic particles, the contact interface performance between the coating and the electrolyte is improved, the wettability of the separator to the electrolyte is enhanced, and the separator melts during thermal anomalies. Close the basement membrane pores and prevent chemical reactions.

Benefits of technology

It improves the electrochemical performance and safety performance of the separator, reduces the risk of thermal runaway of the battery, while maintaining good breathability and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119585935A_ABST
    Figure CN119585935A_ABST
Patent Text Reader

Abstract

The invention discloses a diaphragm and a preparation method thereof, a battery and an electric device. The diaphragm comprises a base film and a coating arranged on at least one surface of the base film, the coating contains organic particles, the organic particles contain nonionic groups, and the volume distribution particle size Dv50 of the organic particles is 1-1.5 [mu] m. The diaphragm provided by the embodiment of the invention simultaneously has good electrolyte infiltration performance and overheating melting response characteristic, so that the barrier property of the diaphragm to transition metal is improved, and the electrochemical performance and the safety performance of the battery are improved. The preparation method can ensure stable performance of the diaphragm structure and the like. The battery comprises the diaphragm.
Need to check novelty before this filing date? Find Prior Art

Description

Diaphragm and preparation method thereof, battery and electrical device Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a diaphragm and a preparation method thereof, a battery, and an electrical device. Background Art

[0002] In the context of energy conservation and emission reduction, new energy technologies are developing rapidly, among which the research breakthroughs and applications of battery technology are the most significant, and lithium-ion batteries are the battery with the most prominent development momentum.

[0003] As battery applications expand, especially in recent years with the rapid development of electric vehicles, power batteries have experienced rapid development and a sharp increase in demand. However, battery safety performance has also received increasing attention and has become one of the key factors restricting the expansion of battery applications.

[0004] Among battery safety issues, the most prominent is the runaway exothermic reaction within the battery. While the emergence of safety-modified separators can improve their safety against thermal runaway to a certain extent, these safety-modified separators also present new challenges, such as reduced electrolyte wettability, which can lead to reduced electrochemical performance, including charge / discharge and cycling performance.

[0005] Summary of the Invention

[0006] In view of the above problems, the embodiments of the present application provide a diaphragm and a preparation method thereof, as well as a battery and an electrical device to solve the technical problem that the existing safety modified diaphragm has unsatisfactory electrolyte wettability.

[0007] In a first aspect, an embodiment of the present application provides a diaphragm. The diaphragm of the embodiment of the present application comprises a base film and a coating disposed on at least one surface of the base film, wherein the coating comprises organic particles, the organic particles comprise nonionic groups, and the volume distribution particle size D of the organic particles is v 50 is 1μm to 1.5μm.

[0008] The separator of the embodiment of the present application modifies the organic particles in the coating with non-ionic groups and controls the particle size to be in the range of 1μm to 1.5μm. On the basis of effectively improving the air permeability of the coating, the contact interface performance between the coating and the electrolyte is effectively improved, thereby effectively improving the wettability of the separator to the electrolyte, thereby improving the electrochemical performance of the battery. Moreover, when the battery is abnormally heated to its melting point, the polymer particles containing non-ionic groups and in this particle size range can melt, thereby sealing the pores contained in the base film, preventing or reducing chemical reactions inside the battery, including crosstalk reactions between the positive and negative electrodes, thereby reducing the risk of thermal runaway of the battery and improving the safety performance of the battery.

[0009] In some embodiments, the molar percentage of the nonionic groups in the organic particles is 0.1% to 5%, and optionally 1% to 3%.

[0010] In some embodiments, the nonionic group is at least one of an ethoxy group, a hydroxyl group, and a carboxylate group.

[0011] The types and contents of non-ionic groups contained in the organic material can further improve the coating quality and air permeability, further improve the affinity of the contact interface between the organic particles and the electrolyte, and thus further improve the wettability of the separator to the electrolyte.

[0012] In some embodiments, the material of the organic particles contains a polymer, and the weight average molecular weight of the polymer is 1,000 to 10,000, and optionally 1,500 to 8,000.

[0013] In an exemplary embodiment, the material of the organic particles contains a polymer, and the polymer includes at least one of polystyrene, polyethylene, polyimide, melamine resin, phenol resin, cellulose, cellulose modifier, polypropylene, polyester, polyphenylene sulfide, polyaramide, polyamideimide, polyimide, and a copolymer of butyl acrylate and ethyl methacrylate.

[0014] By controlling the molecular weight of the organic material of the organic particles and selecting the type of material, the electrolyte wettability of the diaphragm can be further improved and the hot melt response rate during thermal anomalies can be increased.

[0015] In some embodiments, the melting point of the organic particles is 95° C. to 130° C., and optionally 95° C. to 110° C. The organic particles in this melting point range have a relatively sensitive thermal abnormal melting response rate, thereby improving the volatilization effect of the separator of the present application embodiment.

[0016] In some embodiments, the organic particles comprise 18 wt% or greater, and may range from 18 wt% to 32 wt%, based on the total dry weight of the coating as 100%. This range of organic particles can enhance the coating's air permeability and electrolytic affinity, thereby improving the membrane's air permeability and electrolyte wettability, while also enhancing the membrane's melting responsiveness to abnormally high temperatures.

[0017] In some embodiments, the coating further comprises an inorganic particle filler. The presence of the inorganic particle filler can further improve the mechanical properties of the diaphragm, such as wettability, air permeability, and compressive strength.

[0018] In some embodiments, the inorganic particulate filler satisfies at least one of the following conditions:

[0019] (1) Based on the total dry weight of the coating as 100%, the content of the inorganic particulate filler in the coating is 20 wt% to 28 wt%;

[0020] (2) Volume distribution particle size D of the inorganic particle filler v 50 is 1μm to 1.5μm;

[0021] (3) The inorganic particle filler includes at least one of inorganic particles having a dielectric constant of 5 or greater, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of undergoing electrochemical reactions.

[0022] The inorganic particle filler has any of the above characteristics, which can further improve the affinity of the contact interface between the coating and the electrolyte, while improving the air permeability and mechanical properties of the coating, thereby improving the mechanical properties of the diaphragm such as wettability, air permeability and compressive resistance.

[0023] In some embodiments, the coating further comprises a solidified aqueous binder. By adding the binder to the coating, the mechanical strength of the diaphragm can be increased, the air permeability of the diaphragm can be adjusted, and the wettability of the diaphragm can be improved.

[0024] In an embodiment, based on the total dry weight of the coating being 100%, the content of the aqueous binder in the coating is 16 wt % to 28 wt %.

[0025] In an embodiment, the thermal decomposition temperature of the aqueous binder is ≥160°C, and can be selected from 160°C to 300°C.

[0026] The aqueous binder having the above characteristics can enhance the mechanical strength of the separator and can further adjust the wettability and stability of the separator.

[0027] In some embodiments, the base film has a thickness of 4 μm to 7 μm. This thickness of the base film, together with the coating, can effectively reduce the thickness of the separator while improving the coating's wettability, air permeability and other properties, while meeting battery application requirements.

[0028] In some embodiments, the coating has a thickness of 2 μm to 5 μm.

[0029] In some embodiments, the surface density of the coating is 2 g / m 2 Up to 8g / m 2 .

[0030] By controlling characteristics such as coating thickness and surface density, the affinity and permeability of the coating to the electrolyte can be further improved, thereby improving the wettability and permeability of the diaphragm, while also improving the mechanical properties such as compressive resistance and hot melt responsiveness of the diaphragm and sealing the pores of the base membrane.

[0031] In a second aspect, an embodiment of the present application provides a method for preparing a diaphragm. The method for preparing a diaphragm in an embodiment of the present application comprises the following steps:

[0032] Provide a base film and a coating slurry containing organic particles; the organic particles include nonionic groups, and the volume distribution particle size D of the organic particles v 50 is 1μm to 1.5μm;

[0033] The coating slurry is coated on at least one surface of the base film, and dried to form a coating layer to obtain a separator.

[0034] The diaphragm prepared by the diaphragm preparation method of the embodiment of the present application has the good wettability and air permeability of the diaphragm of the embodiment of the text application above, which can effectively reduce the risk of thermal runaway of the battery and improve the electrochemical performance and safety performance of the battery.

[0035] In some embodiments, the coating slurry further comprises an inorganic particle filler and an aqueous binder; wherein the mass ratio of the polymer particles, the inorganic particle filler and the binder in the coating slurry is (18 to 32): (20 to 28): (16 to 28).

[0036] In some embodiments, the coating slurry has a solid content of 30 wt % to 40 wt %.

[0037] In some embodiments, the coating slurry has a viscosity of 100 mPa·s to 1000 mPa·s at 25°C.

[0038] The coating slurry with the above characteristics can improve the film-forming quality, the quality of the coating, and the properties such as wettability and air permeability.

[0039] In some embodiments, when the organic particles are polymer particles containing nonionic groups, the polymer particles are prepared by a method comprising the following steps:

[0040] The polymer precursor particles, the ethoxy-containing polymer and the initiator are mixed and reacted to obtain polymer particles containing nonionic groups;

[0041] The polymer particles containing nonionic groups are emulsified with a nonionic surfactant to obtain a nonionic polymer emulsion.

[0042] By using ethoxylated polymers to carry out polymerization reaction with polymer precursor particles, the nonionic groups contained in the polymer particles can be increased, and in particular, mechanical properties such as compression resistance of the polymer particles can be improved.

[0043] In some embodiments, the polymer precursor particles, the ethoxy-containing polymer, and the initiator are mixed in a ratio of (300 to 400): (90 to 125): (20 to 50).

[0044] In some embodiments, the material of the polymer precursor particles includes at least one of polystyrene, polyolefin, polyimide, melamine resin, phenol resin, cellulose, polyester, polyphenylene sulfide, polyaramid, polyamideimide, and a copolymer of butyl acrylate and ethyl methacrylate.

[0045] In some embodiments, the ethoxy-containing polymer includes at least one of allyl polyethylene glycol and bisallyl polyether.

[0046] In some embodiments, the initiator includes at least one of di-tert-butyl peroxide and dicumyl peroxide.

[0047] In some embodiments, the reaction temperature is 130°C to 140°C.

[0048] In some embodiments, the polymer particles and the nonionic surfactant are emulsified in a mass ratio of (4 to 6):1.

[0049] The above-mentioned reactant types, mixing ratios and reaction conditions can increase the non-ionic group grafting rate and content of the polymer particles and the particle size, improve the affinity of the polymer particles with the electrolyte and the dispersibility in the coating slurry, thereby improving the electrolyte wettability and air permeability of the coating.

[0050] In the embodiment, the nonionic polymer emulsion satisfies at least any one of the following conditions (1) to (4):

[0051] (1) The viscosity of the nonionic polymer emulsion at 25° C. is 10 mPa·s to 100 mPa·s;

[0052] (2) the solid content of the nonionic polymer emulsion is 35 wt% to 40 wt%;

[0053] (3) the pH value of the nonionic polymer emulsion is 5 to 6;

[0054] (4) The nonionic surfactant includes a molecular structure of Wherein, R1 is a carbon chain alkyl group, R2 is a hydrophilic group, and n is a positive integer from 3 to 20.

[0055] In an exemplary embodiment, the carbon chain alkyl group is a long carbon chain alkyl group ranging from C12 to C18.

[0056] In an exemplary embodiment, R2 is at least one of a carboxyl group, an amine group, an aldehyde group, an alcohol group, an amino group, and an amide group.

[0057] In an exemplary embodiment, the nonionic surfactant includes at least one of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, castor oil polyoxyethylene ether, fatty amine polyoxyethylene ether, sorbitan fatty acid ester, and polyoxyethylene sorbitan fatty acid ester.

[0058] By selecting the type of nonionic surfactant, the stability of the nonionic polymer emulsion can be improved, its dispersibility in the coating slurry can be improved, and thus the dispersion uniformity and stability of the polymer particles can be improved.

[0059] In some embodiments, the aqueous binder is added in the form of an aqueous binder aqueous solution, and the aqueous binder aqueous solution has at least one of the following conditions:

[0060] The aqueous binder solution has a viscosity of 3000 mPa·s to 10000 mPa·s at 25° C.;

[0061] The solid content of the aqueous binder solution is 40 wt % to 50 wt %.

[0062] These aqueous binders can improve the stability of the coating slurry and the uniformity of component dispersion, and together with the organic particles, improve the electrolyte wettability and quality of the formed coating, while also improving the mechanical properties and air permeability of the coating.

[0063] In some embodiments, the coating slurry is applied at a rate of 50 m / min to 100 m / min.

[0064] The drying temperature is 60°C to 70°C.

[0065] The drying time is 1 min to 3 min.

[0066] By adjusting the coating process conditions, the film quality, thickness and permeability can be adjusted and optimized.

[0067] In a third aspect, embodiments of the present application provide a battery. The battery of the present application embodiment includes a positive electrode, a negative electrode, and a separator laminated between the positive and negative electrodes, wherein the separator is the separator described in the present application embodiment or a separator prepared by the separator preparation method of the present application embodiment. Because the battery of the present application embodiment includes the separator of the present application embodiment, the battery has high safety and good electrochemical properties such as capacity retention.

[0068] In an embodiment, the coating is provided on one surface of the separator, with the coating facing the negative electrode. By only applying the coating to one surface of the separator, the overall thickness of the separator can be effectively reduced, thereby increasing the energy density of the battery.

[0069] In a fourth aspect, an embodiment of the present application provides an electrical device, wherein the electrical device includes a battery according to an embodiment of the present application, and the battery is used to provide electrical energy. The safety of the electrical device according to the embodiment of the present application is significantly improved.

[0070] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0071] Various other advantages and benefits will become apparent to those skilled in the art upon reading the detailed description of the preferred embodiment below. The accompanying drawings are for illustration purposes only and are not to be considered as limiting the present application. The same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0072] FIG1 is a schematic flow chart of a method for preparing a diaphragm according to an embodiment of the present application;

[0073] FIG2 is a schematic structural diagram of an embodiment of a secondary battery according to an embodiment of the present application;

[0074] FIG3 is an exploded schematic diagram of the secondary battery shown in FIG2 ;

[0075] FIG4 is a schematic structural diagram of an embodiment of a battery module according to the present application;

[0076] FIG5 is a schematic structural diagram of an embodiment of a battery pack according to the present application;

[0077] FIG6 is a schematic diagram of the exploded structure of the battery pack shown in FIG5 ;

[0078] FIG. 7 is a schematic diagram of an embodiment of an electric device including a secondary battery according to an embodiment of the present application as a power source.

[0079] The accompanying drawings in the specific implementation manner are as follows:

[0080] 10. Secondary battery cell, 11. Housing, 12. Electrode assembly, 13. Cover plate;

[0081] 20. Battery module;

[0082] 30. Battery pack, 31. Box, 32. Lower box. DETAILED DESCRIPTION

[0083] The following embodiments of the technical solution of the present application will be described in detail with reference to the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application and are therefore only examples and are not intended to limit the scope of protection of the present application.

[0084] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above-mentioned figure descriptions are intended to cover non-exclusive inclusions.

[0085] In the description of the embodiments of this application, the technical terms "first" and "second" are used only to distinguish different objects and should not be understood to indicate or imply relative importance or implicitly specify the quantity, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, the meaning of "plurality" is more than two, unless otherwise clearly and specifically defined.

[0086] References herein to "embodiments" mean that a particular feature, structure, or characteristic described in connection with the embodiments may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor does it constitute an independent or alternative embodiment that is mutually exclusive of other embodiments. It is understood, both explicitly and implicitly, by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0087] In the description of the embodiments of this application, the term "and / or" is simply a description of the association relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A exists alone, A and B exist simultaneously, and B exists alone. In addition, the character " / " in this document generally indicates that the related objects are in an "or" relationship.

[0088] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0089] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc., indicating the orientation or position relationship, are based on the orientation or position relationship shown in the accompanying drawings, and are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the embodiments of the present application.

[0090] In the description of the embodiments of the present application, unless otherwise expressly specified or limited, technical terms such as "installed," "connected," "connected," and "fixed" should be understood in a broad sense. For example, they can refer to fixed connections, detachable connections, or integration; mechanical connections or electrical connections; direct connections or indirect connections through an intermediate medium; internal connections between two components or interactions between two components. Those skilled in the art can understand the specific meanings of the above terms in the embodiments of the present application based on specific circumstances.

[0091] In the context of energy conservation and emission reduction, new energy technologies are developing rapidly, among which the research breakthroughs and applications of battery technology are the most significant, and lithium-ion batteries are the battery with the most prominent development momentum.

[0092] In ion batteries such as lithium-ion batteries, the diaphragm is one of the important components, which is set between the positive and negative pole pieces to separate the positive and negative poles of the battery, preventing the two poles from contacting and short-circuiting, and preventing the Li-ion battery from passing through the positive and negative poles. + Therefore, in addition to having good electrolyte wettability, liquid retention, and mechanical strength, the separator also needs to have properties such as thermal stability that have a significant impact on battery safety, as battery safety performance is increasingly valued.

[0093] Currently, the method of improving the thermal stability and other properties of the diaphragm is to modify the diaphragm, such as doping or coating modifiers such as flame retardant additives, fiber-like substances, electrochemically inert ceramics, etc. during the preparation process of the diaphragm, so as to achieve the purpose of improving the thermal stability and other properties of the diaphragm and thus improving battery safety.

[0094] While current methods like doping or coating can improve the thermal stability and other properties of the separator to a certain extent, the inventors discovered during their research that when the exothermic reaction within the battery accumulates to a certain level, the modified separator is unable to promptly block the continued reaction within the battery, making it difficult to delay or suppress the exothermic reaction, which can lead to runaway. Therefore, this approach is not ideal for improving battery safety, such as thermal runaway.

[0095] To improve the diaphragm's ability to suppress battery thermal runaway, current methods include modifying the diaphragm surface, such as adding a modified coating. However, the inventors discovered in their research that adding a modified coating to the diaphragm actually adversely affects the diaphragm's air permeability. Therefore, the inventors proposed a modified diaphragm, specifically adding a coating containing organic particles to the diaphragm. While ensuring good air permeability, the coating can also melt and seal the pores of the diaphragm to form a blocking barrier layer when overheating occurs inside the battery, reducing or preventing reactions inside the battery, thereby reducing the risk of thermal runaway and improving battery safety.

[0096] Based on this, the inventors further discovered that the particle size of the organic particles contained in the modified separator coating and the grafting modification treatment of these organic particles significantly affect the electrolyte wettability of the modified separator. Therefore, the inventors controlled the particle size of the organic particles within a certain range and simultaneously modified the organic particles with groups. Through the synergistic effect of these two treatments, the organic particles were given good affinity with the electrolyte and film-forming quality, which effectively improved the interfacial contact performance between the coating and the electrolyte, thereby significantly improving the electrolyte wettability of the modified separator.

[0097] diaphragm

[0098] In a first aspect, an embodiment of the present application provides a diaphragm. The diaphragm of the embodiment of the present application comprises a base film and a coating disposed on at least one surface of the base film. The coating contains organic particles, and the volume distribution particle size D of the organic particles is v 50 is 1 μm to 1.5 μm, and the organic particles include nonionic groups.

[0099] In the separators of the present invention, the base film comprises the substrate of the separators of the present invention and performs the usual functions of a separator. The coating is disposed on the base film and modifies the base film, i.e., the separator substrate. For example, the coating improves the pore structure of the base film and the interface between the coating and the electrolyte, thereby improving the separator's wettability to the electrolyte. When the battery overheats, the organic particles melt and seal the pores in the base film.

[0100] The volume distribution particle size D of the organic particles contained in the coating of the diaphragm of the embodiment of the present application is v 50 is 1 μm to 1.5 μm, and the coating formed by the organic particles in this particle size range on the base film can form a specific pore structure, thereby giving the diaphragm a specific electrolyte path on the basis of good air permeability. On this basis, organic particles containing non-ionic groups are selected, and the coating formed therefrom has good affinity with the electrolyte contact interface. Therefore, the diaphragm of the embodiment of the present application, through the combined effect of the particle size of the organic particles contained in its coating and the non-ionic groups contained therein, gives the diaphragm of the embodiment of the present application a good affinity with the electrolyte on the basis of good air permeability, so that the electrolyte wettability of the diaphragm of the embodiment of the present application is significantly improved, thereby significantly improving the electrochemical properties of the battery including charging and discharging, cyclability, etc.

[0101] Moreover, the organic particles in this particle size range and the non-ionic groups contained therein can significantly improve the sensitive hot melt response rate of the organic particles. When the battery has a thermal anomaly, such as when the temperature rises to the melting point of the organic particles, the organic particles can melt in time and close the pores contained in the base film, thereby reducing or preventing the chemical reactions inside the battery, including those in the electrolyte, the migration of metal ions, and the positive and negative electrode crosstalk reactions, alleviating or terminating the thermal runaway of the battery, thereby improving the safety performance of the battery. Among them, the migration of the metal ions includes lithium ions and metal precipitation from active materials, etc., to prevent them from passing through the diaphragm and depositing on the surface of the electrode, especially the negative electrode, or further forming dendrites. The positive and negative electrode crosstalk reaction refers to the release of oxygen when the positive electrode active material of the battery undergoes a phase change at high temperature. The oxygen can diffuse through the diaphragm to the negative electrode and react with the negative electrode, etc., and release a large amount of heat; it also includes the hydrogen released from the negative electrode at high temperature, which diffuses through the diaphragm to the positive electrode and reacts with the positive electrode, etc., and releases a large amount of heat.

[0102] In the exemplary embodiment, the volume distribution particle size D of the organic particles is v 50 can be a limited but non-limiting particle size range of 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, etc., and can be selected from 1.2 μm to 1.4 μm. By further adjusting the particle size D of the organic particles v 50, can enhance the above-mentioned role of organic particles, further improve the pore structure of the coating, and improve the electrolyte wettability of the diaphragm and the hot melt response rate in the event of thermal anomaly.

[0103] In some embodiments, the molar percentage of the non-ionic groups contained in the organic material of the organic particles is 0.1% to 5%, optionally 1% to 3%, and specifically can be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc., which are limited but non-restrictive molar contents. In an exemplary embodiment, the non-ionic group can include at least one of an ethoxy group, a hydroxyl group, and a carboxylate group. By controlling the content and type of the non-ionic group in the organic material, the above-mentioned effects of the organic particles can be further enhanced, in particular, the electrolyte affinity of the organic particles can be improved, and the dispersion uniformity of the polymer particles in the coating and the film quality of the coating can be improved, thereby improving the electrolyte wettability and air permeability of the diaphragm. It is also possible to adjust the melting point range of the organic particles and improve their hot melt response rate.

[0104] The organic material of the organic particles in the above embodiments can be a polymer or other small molecule organic matter, or a mixture of small molecules and polymers, as long as the volume distribution particle size D of the organic particles formed by the organic material is v 50 is 1 μm to 1.5 μm, all within the range disclosed in the embodiments of the present application.

[0105] In some embodiments, when the organic material of the organic particles in the above embodiments includes a polymer, the organic particles may be polymer particles. In some embodiments, the polymer may have a weight-average molecular weight of 1,000 to 10,000, optionally 1,500 to 8,000. The molecular weight can be determined using gel permeation chromatography (GPC) with reference to GBT 27843-2011, "Test Method for Low Molecular Weight Component Content in Chemical Polymers."

[0106] In exemplary embodiments, the polymer may include at least one of polystyrene, polyolefin, polyimide, melamine resin, phenolic resin, cellulose, polyester, polyphenylene sulfide, polyaramid, polyamide-imide, copolymers of butyl acrylate and ethyl methacrylate, and modified polymers thereof. By controlling the melting point of the organic material and selecting the right material for the organic particles, the aforementioned effects of the organic particles can be further enhanced, further improving the electrolyte wettability of the separator and increasing the melt response rate during thermal anomalies.

[0107] When the organic material of the organic particles includes a polymer, the nonionic groups contained in the organic material can be grafted side chains of the polymer or connected to the main chain of the polymer.

[0108] In the embodiment, the melting point of the organic particles in the above embodiments is controlled at 90°C to 130°C, and can further be in the range of 95°C to 110°C. The organic particles in this melting point range have a relatively sensitive hot melt response rate during thermal anomalies, and have good affinity with the electrolyte, thereby improving the volatilization effect of the above-mentioned effect of the diaphragm of the embodiment of the present application. Among them, the melting point can be measured by a universal differential scanning calorimeter (DSC) method with reference to the standard ISO 11357-3-2018.

[0109] In some embodiments, in each of the above embodiments, the content of organic particles in the coating can be ≥18wt%, and further can be 18wt% to 32wt%, based on the total weight (dry weight) of the coating as 100%. By controlling and adjusting the content of organic particles in the coating, if controlled within this range, it is possible to improve the permeability of the coating and the affinity of the coating to the electrolyte contact interface, thereby improving the permeability of the diaphragm and the wettability of the electrolyte, thereby improving the electrochemical performance of the battery. At the same time, it can improve the responsiveness of the diaphragm to abnormal heating and the effect of melting and sealing the pores of the base membrane, thereby improving the safety performance of the battery.

[0110] In some embodiments, the morphology of the organic particles contained in the coating can include at least one of chain, spherical, quasi-spherical, fibrous, tubular, rod-shaped, amorphous, and pyramidal shapes. Organic particles with these morphologies can improve the electrolyte wettability and air permeability of the coating, thereby improving the electrolyte wettability and air permeability of the separator and enhancing the electrochemical performance of the battery. When the battery experiences thermal anomalies, the organic particles with these morphologies have a high thermal melt response rate, accelerating the closure of the basement membrane pores. Therefore, organic particles with these morphologies can further reduce the risk of thermal runaway and improve battery safety.

[0111] In addition, the organic particles in the above embodiments can be solid particles, and of course they can also be hollow particles. In the embodiments of the present application, solid particles can improve the compressive resistance of the organic particles compared to hollow particles, thereby improving the stability of the coating during battery production and normal operation. For example, the organic particles will not be deformed due to the squeezing force during battery production or use, thereby causing pore blockage in the basement membrane. Therefore, in the embodiments of the present application, solid organic particles are relatively preferred compared to hollow organic particles.

[0112] In some embodiments, the coatings included in the separators of the aforementioned embodiments further contain inorganic particulate fillers. Adding inorganic particulate fillers to the coatings can, on the one hand, improve the coating's mechanical properties, such as compressive strength, and enhance the separator's stability during battery production and normal operation. Furthermore, they can act synergistically with the aforementioned organic particles, further enhancing the coating's compatibility with the electrolyte and improving the coating's pore structure. This, in turn, improves the separator's air permeability, liquid storage capacity, and mechanical properties, such as thermal shrinkage resistance, while also enhancing the separator's responsiveness to hot melt. Furthermore, the inorganic particulate fillers ideally form a mixture with the aforementioned organic particles in the coating.

[0113] In the embodiment, the content of the inorganic particulate filler in the coating can be 20 wt % to 28 wt % based on the total weight (dry weight) of the coating as 100%. By controlling the content ratio of the inorganic particulate filler and the organic particles in the coating, the synergistic effect between the two can be enhanced while fully evaporating the respective effects described above. This further improves the electrolyte wettability and air permeability of the separator, as well as the hot melt response efficiency, while ensuring good air permeability and mechanical properties of the separator.

[0114] In the embodiment, the volume distribution particle size D of the inorganic particle filler is v 50 is 1 μm to 1.5 μm. By adjusting the inorganic particle filler, it is compounded with the organic particle size, such as controlling the D vThe inorganic filler particles have a particle size range of 1μm to 1.5μm, acting as a coating skeleton, improving the coating's compressive strength and other mechanical properties. They also work together with the organic particles in the aforementioned particle size range to enhance the permeability and wettability of the separator. Testing has shown that the separator's permeability can reach the permeability shown in Table 1 below. Furthermore, when the battery experiences abnormal thermal heating and reaches the melting point of the organic particles, the inorganic particles in this particle size range can fully exert their skeleton function, causing the organic particles to melt and seal the pores of the base membrane. They also work together with the base membrane to isolate the positive and negative electrodes, reducing the risk of short-circuit thermal runaway.

[0115] In an embodiment, the inorganic particle filler may include at least one of inorganic particles having a dielectric constant of 5 or greater, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of undergoing electrochemical reactions.

[0116] In an exemplary embodiment, the inorganic material of the inorganic particles having a dielectric constant of 5 or more includes boehmite, aluminum oxide, zinc oxide, silicon oxide, titanium oxide, zirconium oxide, barium oxide, calcium oxide, magnesium oxide, nickel oxide, tin oxide, cerium oxide, yttrium oxide, hafnium oxide, aluminum hydroxide, magnesium hydroxide, silicon carbide, boron carbide, aluminum nitride, silicon nitride, boron nitride, magnesium fluoride, calcium fluoride, barium fluoride, barium sulfate, magnesium aluminum silicate, lithium magnesium silicate, sodium magnesium silicate, bentonite, hectorite, zirconium titanate, barium titanate, Pb(Zr,Ti)O3, Pb 1-m La m Zr 1-n TinO3、Pb(Mg3Nb 2 / 3 )O3-PbTiO3, and at least one of their respective modified inorganic particles, 0<m<1, 0<n<1.

[0117] In an exemplary embodiment, the inorganic material of the inorganic particles having ion conductivity but not storing ions includes Li3PO4, lithium titanium phosphate Li x1 Ti y1 (PO4)3, lithium aluminum titanium phosphate Li x2 Al y2 Ti z1 (PO4)3, (LiAlTiP) x3 O y3 Type glass, lanthanum lithium titanate Li x4 La y4 TiO3, lithium germanium thiophosphate Li x5 Ge y5 P z2 S w , lithium nitride Li x6 N y6 、SiS2 type glass Li x7 Si y7 S z3 and P2S5 glass Lix8 P y8 S z4 At least one of , 0<x1<2, 0<y1<3, 0<x2<2, 0<y2<1, 0<z1<3, 0<x3<4, 0<y3<13, 0<x4<2, 0<y4<3, 0<x5<4, 0<y5<1, 0<z2<1, 0<w<5, 0<x6<4, 0<y6<2, 0<x7<3, 0<y7<2, 0<z3<4, 0<x8<3, 0<y8<3, 0<z4<7;

[0118] In an exemplary embodiment, the inorganic material of the electrochemically reactive inorganic particles includes at least one of lithium-containing transition metal oxides, lithium-containing phosphates, carbon-based materials, silicon-based materials, tin-based materials, and lithium-titanium compounds.

[0119] By carefully selecting the type of inorganic particle filler material, the aforementioned effects of the inorganic particle filler are enhanced, and the synergistic effect between the inorganic particle filler and the organic particles is further enhanced, thereby improving the electrolyte wettability, air permeability, and mechanical properties of the coating layer (i.e., the separator) of the present application embodiment, and improving the electrochemical performance and safety performance of the battery, such as the capacity retention rate. In particular, the inorganic particle fillers of some of the aforementioned inorganic materials also have good liquid absorption and storage capabilities, thereby improving the liquid absorption and storage capabilities of the separator.

[0120] Based on the above organic and inorganic particulate fillers, in this exemplary embodiment, the polymer contained in the organic particles of the coating is low-density polyethylene, specifically low-density polyethylene particles, and further, low-density polyethylene containing non-ionic groups. The low-density polyethylene refers to high-pressure polyethylene (LDPE), specifically polyethylene with a molecular weight of less than 10,000.

[0121] The above-mentioned inorganic particles are compounded with the low-density polyethylene particles to enhance the above-mentioned synergistic effect between the organic particles and the inorganic particle fillers, thereby improving the electrolyte wettability, air permeability and stability of the coating of the embodiment of the present application, that is, the diaphragm, and at the same time improving the liquid absorption and storage capacity of the diaphragm.

[0122] In some embodiments, the coating contained in the diaphragm of each of the above embodiments further contains a solidified aqueous binder. By adding an aqueous binder to the coating, the bonding force between the organic particles or the inorganic particle fillers can be effectively enhanced, thereby improving the mechanical properties of the coating such as compressive strength, and enhancing the bonding force between the coating and the base film. At the same time, the aqueous binder can also play a synergistic role with the organic particles or further with the inorganic particle fillers, adjusting the wettability and air permeability of the coating, that is, the diaphragm, and improving the hot melt responsiveness of the organic particles to seal the pores of the base film, thereby improving the electrochemical performance and safety performance of the battery, such as the capacity retention rate.

[0123] In an embodiment, the content of the aqueous binder in the coating can be 16 wt % to 28 wt % based on the total weight (dry weight) of the coating as 100%. By controlling the content of the aqueous binder in the coating, the mechanical properties of the coating and the adhesion between the coating and the base film can be further enhanced, thereby further adjusting the wettability, air permeability, and stability of the coating, i.e., the separator.

[0124] In an embodiment, the thermal decomposition temperature of the cured aqueous binder is higher than 160°C, and can be selected from 160°C to 300°C. By selecting the decomposition temperature characteristics of the aqueous binder, the mechanical properties of the coating and the bonding between the coating and the base membrane are enhanced, and the compressive resistance and air permeability of the separator, as well as its operational stability, are improved. This allows the organic particles to melt and seal the pores of the base membrane when the battery experiences thermal anomalies, while also improving the insulation of the separator and reducing the risk of thermal runaway.

[0125] In an embodiment, the aqueous binder may be a water-soluble binder or an emulsion binder. In an exemplary embodiment, the aqueous binder may include at least one of polyvinyl alcohol, polyacrylic acid-polyacrylonitrile copolymer, polyacrylate-polyacrylonitrile copolymer, polyether acrylate, polyurethane, polyacrylate, polycarbonate, polyethylene oxide, rubber, polyacrylic acid, polyacrylonitrile, gelatin, chitosan, sodium alginate, cyanoacrylate, polymerized cyclic ether derivatives, and hydroxyl derivatives of cyclodextrin. These aqueous binders can enhance the bonding force between organic particles or further inorganic particle fillers, thereby improving the mechanical properties of the coating and enhancing the bonding force between the coating and the base film. Further adjust the electrolyte wettability, air permeability and working stability of the diaphragm.

[0126] In an embodiment, when the coating contains both the above-mentioned inorganic particle filler and the aqueous binder, the dry weight ratio of the above-mentioned organic particles, inorganic particle filler, and aqueous binder in the coating can be (18 to 32): (20 to 28): (16 to 28). By controlling the content ratio of the three components in the coating, the above-mentioned effects of each component and the synergistic effect between the three components are further enhanced, thereby further improving the pore structure of the coating, improving the wettability, air permeability, working stability, and liquid storage capacity of the coating, i.e., the diaphragm, and thereby improving the electrochemical properties and safety performance of the battery, such as the capacity retention rate.

[0127] Based on the coating schemes in the above embodiments, in some embodiments, the coating thickness can be 2μm to 5μm. In exemplary embodiments, the coating thickness can be 2μm, 3μm, 4μm, 5μm, and other typical but non-limiting thicknesses. By controlling the coating thickness, the content of components such as organic particles can be controlled, thereby further regulating and improving the ability of the organic particles to fully exert the functions described above, improving the melting and effective sealing of the pores of the base film in the event of thermal anomalies in the battery, reducing or preventing the risk of thermal runaway, and simultaneously improving the mechanical properties of the coating, i.e., the separator, such as electrolyte wettability, air permeability, and compressive strength, thereby improving the electrochemical performance and safety performance of the battery, such as capacity retention.

[0128] After testing, the surface density of the coating contained in the above-mentioned embodiments can be controlled at 2g / m 2 Up to 8g / m 2 , optional 2g / m 2 Up to 4g / m 2 By controlling and optimizing these properties of the coating, the membrane's wettability to the electrolyte, air permeability, and operational stability can be further improved, thereby further improving the electrochemical performance and safety of the battery.

[0129] Furthermore, the coating included in the separators of the above embodiments can be disposed on one surface of the base membrane, or alternatively, on two opposing surfaces of the base membrane. Based on considerations such as battery energy density and dendrite formation characteristics, in the embodiments, the coating is disposed on one surface of the base membrane, meaning that the coating is not disposed on the opposing surface of the base membrane.

[0130] The base film contained in the separator of each embodiment above can be a battery organic separator. For example, in the embodiment, the conductive thickness of the base film can be 4μm to 7μm. In other embodiments, the air permeability of the base film can be 180s / 100cc to 240s / 100cc. In the exemplary embodiment, the material of the base film includes at least one of non-woven fabric, polyolefin, polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene ether, polyphenylene sulfide, and polyethylene naphthalene. The base film with these characteristics and materials can be combined with the above coating and play a synergistic role on the basis of giving full play to the role of the battery separator, thereby improving the electrolyte wettability and air permeability of the separator, effectively reducing the risk of thermal runaway of the battery, and improving the electrochemical performance and safety performance of the battery such as the capacity retention rate.

[0131] In some embodiments, the above-mentioned base membrane can also be a modified base membrane, such as a base membrane modified with at least one modifier such as flame retardants, fiber-like substances, electrochemically inert ceramics, etc., to improve the thermal stability of the base membrane, to cooperate with the above-mentioned coating, and further improve the mechanical properties and safety performance of the diaphragm of the embodiment of the present application.

[0132] Method for preparing diaphragm

[0133] In a second aspect, the present invention provides a method for preparing a diaphragm. The process flow of the method for preparing a diaphragm according to the present invention is shown in FIG1 . The method for preparing a diaphragm according to the present invention may include the following steps:

[0134] S01: providing a basement membrane;

[0135] S02: providing coating slurry;

[0136] S03: coating the coating slurry on at least one surface of the base film, performing a drying process to form a coating layer, and obtaining a separator.

[0137] In the preparation method of the diaphragm of the embodiment of the present application, after the coating slurry is formed on the surface of the base film, the coating is bonded to the surface of the base film. Since the preparation method of the diaphragm of the embodiment of the present application is to prepare the diaphragm of the embodiment of the present application, the formed coating contains organic particles, and the volume distribution particle size D of the organic particles is v 50 is 1 μm to 1.5 μm, and the organic particles contain nonionic groups.

[0138] The diaphragm preparation method of the embodiment of the present application directly forms a film on the base film with a slurry containing non-ionic groups and organic particles of this particle size range, so that the prepared diaphragm is combined with a coating on at least one surface to achieve the modification effect of the coating on the base film. Then the coating is the coating contained in the diaphragm of the embodiment of the above text application. Therefore, the diaphragm prepared by the diaphragm preparation method of the embodiment of the present application has the good electrolyte wettability and air permeability as the diaphragm of the embodiment of the above text application, or further has high mechanical properties such as compressive resistance and hot melt responsiveness, which can effectively further reduce the risk of thermal runaway of the battery and further improve the electrochemical properties and safety performance of the battery such as the capacity retention rate. In addition, the process parameters of the diaphragm preparation method of the embodiment of the present application are controllable, and the quality and electrochemical properties of the prepared diaphragm are stable.

[0139] Step S01:

[0140] The base film in step S01 can be the base film contained in the separator of the embodiment of the above-mentioned application. Therefore, the base film can be the base film contained in the separator of the embodiment of the above-mentioned application. As in the embodiment, the thickness of the provided base film can be 4μm to 7μm, and its air permeability can be 180s / 100cc to 240s / 100cc. Its material can include at least one of non-woven fabric, polyolefin, polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalene.

[0141] Step S02:

[0142] Since the coating slurry in step S02 is a slurry for forming the coating contained in the diaphragm of the above text application embodiment, the slurry must contain organic particles and a solvent. In the embodiment, it may further contain an inorganic particle filler and an aqueous binder. Therefore, the organic particles contained in the coating slurry, or the material types and content ratios of the inorganic particle fillers and aqueous binders further contained therein are the same as the types and content ratios of the organic particles, inorganic particle fillers and aqueous binders contained in the coating of the diaphragm of the above text application embodiment. Therefore, in order to save space, the types, content ratios, etc. of organic particles, inorganic particle fillers and aqueous binders will not be described in detail here.

[0143] In order to improve the film-forming quality of the coating slurry, improve the quality of the coating and the diaphragm, as well as the wettability, air permeability and other properties, in one embodiment, the solid content of the coating slurry can be 30wt% to 40wt%; in other embodiments, the viscosity of the coating slurry at 25°C is 100mPa·s to 1000mPa·s.

[0144] In some embodiments, when the coating slurry in step S02 is formed by mixing organic particles, inorganic particle fillers and aqueous binders in a solvent; then the mass ratio of organic particles, inorganic particle fillers, aqueous binders and water in the coating slurry can be (18 to 32): (20 to 28): (16 to 28): (23 to 33). This ratio refers to the mixing ratio of aqueous binder to organic particles and inorganic particle fillers before curing. By adjusting the ratio of the three, the film-forming quality of the coating slurry is improved, and at the same time, the electrolyte wettability, air permeability, compressive strength and other properties of the coating, that is, the prepared diaphragm, are enhanced, thereby further improving the electrochemical performance of the battery and reducing the risk of thermal runaway of the battery.

[0145] Among them, the aqueous binder should be an aqueous binder before curing, such as the aqueous binder before curing described above. In an exemplary embodiment, the aqueous binder before curing may include at least one of polyvinyl alcohol, polyacrylic acid-polyacrylonitrile copolymer, polyacrylate-polyacrylonitrile copolymer, polyether acrylate, polyurethane, polyacrylate, polycarbonate, polyethylene oxide, rubber, polyacrylic acid, polyacrylonitrile, gelatin, chitosan, sodium alginate, cyanoacrylate, polymerized cyclic ether derivatives, and hydroxyl derivatives of cyclodextrin.

[0146] For example, in the embodiments, the aqueous binder is added as an aqueous binder solution to effectively adjust the viscosity of the coating slurry, improve the dispersion uniformity and stability of the coating slurry components, and improve the film-forming quality of the coating slurry. When the aqueous binder is added as an aqueous binder solution, in the embodiments, the viscosity of the aqueous binder solution at 25°C can be 3000mPa·s to 10000mPa·s; in other embodiments, the solid content of the aqueous binder solution is 40wt% to 50wt%. By controlling and adjusting the viscosity of the aqueous binder solution or the solid content at the same time, the positive effect of the aqueous binder on the coating slurry can be further enhanced, further improving the slurry stability and dispersibility.

[0147] In the embodiment, when the organic particles contained in the coating slurry are polymer particles containing nonionic groups, the polymer particles can be prepared according to a method comprising the following steps:

[0148] Step S021: mixing and reacting polymer precursor particles, an ethoxy-containing polymer, and an initiator to obtain polymer particles containing nonionic groups;

[0149] Step S022: emulsifying the polymer particles containing nonionic groups with a nonionic surfactant to obtain a nonionic polymer emulsion.

[0150] During the reaction process of step S021 , the polymer precursor particles and the ethoxy-containing polymer undergo a polymerization reaction under the action of an initiator, so that the ethoxy-containing group is grafted onto the polymer particles.

[0151] In the embodiment, the polymer precursor particles, the ethoxy-containing polymer and the initiator are mixed in a mass ratio of (300 to 400): (90 to 125): (20 to 50).

[0152] In an embodiment, the reaction temperature in step S021 may be 130° C. to 140° C., and the reaction time should be sufficient, such as 2.5 to 4 hours at 130° C. to 140° C. Meanwhile, during the reaction, the molten reactants are stirred to improve the reaction efficiency and uniformity.

[0153] By controlling and adjusting the mixing ratio of the reactants in step S021, or further controlling the reaction conditions, the particle size of the polymer particles can be adjusted to the value set above D based on the improvement of the polymer reaction efficiency. v On the basis of the range of 50 being 1 μm to 1.5 μm, the content of ethoxylated nonionic groups grafted onto the polymer particles is increased, thereby improving the nonionic group modification effect of the polymer particles, thereby improving the above effects of the polymer particles, especially improving the hydrophilicity, dispersibility and film-forming uniformity of the polymer particles.

[0154] In an exemplary embodiment, the material of the polymer precursor particles may include at least one of polystyrene, polyolefin, polyimide, melamine resin, phenol resin, cellulose, polyester, polyphenylene sulfide, polyaramid, polyamideimide, and a copolymer of butyl acrylate and ethyl methacrylate.

[0155] The ethoxy group-containing polymer may include at least one of allyl polyethylene glycol and bisallyl polyether.

[0156] The initiator may include at least one of di-tert-butyl peroxide and dicumyl peroxide.

[0157] The polymer precursor particles, ethoxylated polymer, and initiator can undergo a polymerization reaction in step S021 to improve the efficiency of graft modification. The ethoxylated polymer can effectively provide ethoxylated nonionic groups to achieve graft modification of the ethoxylated nonionic groups of the polymer precursor particles.

[0158] In step S022, during the emulsification process, a nonionic surfactant and nonionic group-containing polymer particles are combined in a solvent to form an emulsion. In embodiments, the mass ratio of the nonionic group-containing polymer particles to the nonionic surfactant can be (4 to 6):1, and in an exemplary embodiment, 4.5:1. The solvent can be water.

[0159] In addition, the mixing ratio of the nonionic surfactant and the polymer particles containing nonionic groups, as well as the amount of added aqueous solvent, can be controlled to adjust and control the relevant properties of the nonionic polymer emulsion, such as viscosity, solid content, pH value, etc., thereby improving the dispersion uniformity and stability of the polymer particles in the coating slurry, thereby improving the above-mentioned effect of forming the coating and improving the electrochemical performance and safety performance of the prepared separator. For example, by controlling and adjusting the conditions of the emulsification treatment in step S022, the nonionic polymer emulsion has at least one of the following properties:

[0160] (1) The viscosity of the nonionic polymer emulsion is 10 mPa·s to 100 mPa·s;

[0161] (2) the solid content of the nonionic polymer emulsion is 35 wt % to 40 wt %;

[0162] (3) The pH value of the nonionic polymer emulsion is 5 to 6.

[0163] Among them, the mixing ratio of the nonionic surfactant and the polymer particles can effectively adjust the viscosity and solid content of the nonionic polymer emulsion, thereby improving the dispersibility of the polymer particles and improving the uniformity and stability of the coating slurry.

[0164] In some embodiments, the nonionic surfactant may include a molecular structure of

[0165] Wherein, R1 is a carbon chain alkyl group. In an exemplary embodiment, when it is a carbon chain alkyl group, R1 is a long carbon chain alkyl group of C12 to C18.

[0166] R2 is a hydrophilic group. In an exemplary embodiment, R2 is at least one of a carboxyl group, an amine group, an aldehyde group, an alcohol group, an amino group, and an amide group.

[0167] n is a positive integer from 3 to 20. In the examples, n can be a typical but non-limiting positive integer such as 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20.

[0168] In an exemplary embodiment, the nonionic surfactant includes at least one of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, castor oil polyoxyethylene ether, fatty amine polyoxyethylene ether, sorbitan fatty acid ester, and polyoxyethylene sorbitan fatty acid ester.

[0169] By selecting the type of nonionic surfactant, the stability of the nonionic polymer emulsion can be improved, its dispersibility in the coating slurry can be improved, and thus the dispersion uniformity and stability of the polymer particles can be improved.

[0170] In addition, there is no specific order between step S01 and step S02 above. The order can be adjusted according to actual production, or they can be performed simultaneously.

[0171] Step S03:

[0172] The coating slurry is applied to the base film in step S02 to form a wet film, i.e., the coating layer before drying. The coating method is not limited to any method capable of forming a film of the coating slurry on the base film, and is within the scope of the embodiments disclosed herein. Examples include, but are not limited to, brushing, roller coating, and spraying. Furthermore, the coating process conditions can be further adjusted to optimize the film quality, thickness, and air permeability.

[0173] In the embodiment, the coating slurry in step S02 can be applied at a rate of 50 m / min to 100 m / min. In exemplary embodiments, the rate can be 50 m / min, 60 m / min, 70 m / min, 80 m / min, 90 m / min, 100 m / min, and other typical but non-limiting rates. This coating rate can improve the quality of the coating and adjust the air permeability and thickness. This coating rate can improve the quality of the coating and adjust the air permeability and thickness.

[0174] The drying process is primarily intended to remove solvent from the wet film. Based on the melting temperature range of the organic particles contained in the coating slurry, the drying temperature should be below the melting temperature of the organic particles and should ensure coating quality and stability. For example, in the embodiment, the drying temperature can be 50°C to 70°C. In exemplary embodiments, typical but non-limiting temperatures such as 50°C, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, and 70°C can be used. Within this drying temperature range, the drying time should be sufficient, such as 1 to 3 minutes.

[0175] Battery

[0176] In a third aspect, an embodiment of the present application provides a battery comprising a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, wherein the separator is the separator of the embodiment of the present application.

[0177] In the examples, the separator is coated only on one surface, with the coated surface facing the negative electrode. By orienting the coating toward the negative electrode, the separator can fully utilize the functions described in the examples above, further improving the battery's electrochemical performance, reducing the risk of thermal runaway, and enhancing battery safety. Furthermore, by only coating the separator on one surface, the overall thickness of the separator can be effectively reduced, thereby increasing the battery's energy density.

[0178] In some embodiments, the battery of the present application can be a secondary battery. When the battery of the present application is a secondary battery, it includes a positive electrode, a separator, and a negative electrode. Specifically, the negative electrode of the secondary battery is the negative electrode of the embodiment described above, and the negative electrode contains the modified artificial graphite of the embodiment described above.

[0179] In this way, the battery of the embodiment of the present application, specifically the secondary battery, has high energy density, high rate capability and good cycle stability.

[0180] In an embodiment, the secondary battery of the present application may include any one of a battery cell, a battery module, and a battery pack.

[0181] A battery cell is a structure that includes a battery housing and a cell encapsulated within the housing. The shape of a battery cell is not particularly limited and can be cylindrical, square, or any other shape. A square-shaped battery cell 10 is shown in FIG2 .

[0182] In some embodiments, as shown in Figure 3, the outer packaging of the battery cell 10 may include a shell 11 and a cover plate 13. The shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 is used to cover the opening to close the receiving cavity. The positive electrode, diaphragm and negative electrode contained in the secondary battery of the embodiment of the present application can be formed into an electrode assembly 12 through a winding process and / or a lamination process. The electrode assembly 12 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 12. The number of electrode assemblies 12 contained in the battery cell 10 can be one or more, which can be adjusted according to actual needs.

[0183] The preparation method of the battery cell 10 is well known. In some embodiments, the positive electrode, separator, negative electrode, and electrolyte can be assembled to form the battery cell 10. As an example, the positive electrode, separator, and negative electrode can be wound or laminated to form the electrode assembly 12. The electrode assembly 12 is placed in an outer package, dried, and then injected with electrolyte. The battery cell 10 is then vacuum packaged, allowed to stand, formed, and shaped.

[0184] A battery module is assembled from the battery cells 10 , that is, it may contain a plurality of battery cells 10 , and the specific number can be adjusted according to the application and capacity of the battery module.

[0185] In some embodiments, FIG4 is a schematic diagram of an exemplary battery module 20. As shown in FIG4 , in the battery module 20, multiple battery cells 10 may be arranged sequentially along the length of the battery module 20. Of course, any other arrangement is also possible. Furthermore, the multiple battery cells 10 may be secured together using fasteners.

[0186] Optionally, the battery module 20 may further include a housing having an accommodation space, and the plurality of battery cells 10 may be accommodated in the accommodation space.

[0187] A battery pack is assembled from the battery cells 10 described above, and may contain multiple battery cells 10, wherein multiple battery cells 10 may be assembled into the battery module 20 described above. The specific number of battery cells 10 or battery modules 20 contained in a battery pack may be adjusted according to the application and capacity of the battery pack.

[0188] In the embodiment, Figures 5 and 6 are schematic diagrams of an exemplary battery pack 30. The battery pack 30 may include a battery box and multiple battery modules 20 disposed within the battery box. The battery box includes an upper box body 31 and a lower box body 32. The upper box body 31 covers the lower box body 32 and forms an enclosed space for accommodating the battery modules 20. The multiple battery modules 20 may be arranged in any manner within the battery box.

[0189] Electrical devices

[0190] Fourthly, embodiments of the present application further provide an electrical device comprising the battery of the aforementioned embodiments, which may further comprise a secondary battery. The battery can serve as both a power source and an energy storage unit for the electrical device. Consequently, the electrical device of the embodiments of the present application has a long standby or battery life.

[0191] Electrical devices may include, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, energy storage systems, etc. These electrical devices may use secondary batteries, battery modules, or battery packs based on their usage requirements.

[0192] Figure 7 is a schematic diagram of an exemplary electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of this device, a battery pack or battery module may be used.

[0193] As another example, the electric device may be a mobile phone, a tablet computer, a laptop computer, etc. Such an electric device is usually required to be lightweight and thin, and may use a secondary battery as a power source.

[0194] Example

[0195] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.

[0196] 1. Diaphragm and its preparation method embodiment

[0197] Example A1

[0198] This embodiment provides a separator and a method for preparing the same. The separator comprises a PE base film and a coating bonded to one surface of the PE base film. The PE base film is 7 μm thick, and the coating is 3 μm thick. The coating contains copolymerized polypropylene wax particles containing ethoxy groups. Testing revealed that the polymer particles, including particle size, exhibited the following parameters:

[0199] The diaphragm preparation method of this embodiment includes the following steps:

[0200] S1. Preparation of coating slurry:

[0201] S11. Preparation of organic particles:

[0202] a. According to the copolymerized polypropylene wax: allyl polyethylene glycol: initiator = 300:100:20 ratio, the copolymerized polypropylene wax, allyl polyethylene glycol, di-tert-butyl peroxide were mixed and heated to melt and stirred uniformly, and the intermediate product was obtained after a constant temperature of 160 ℃ and 3h;

[0203] b. Mix the intermediate product and nonionic emulsifier (fatty alcohol polyoxyethylene ether AEO-3) in a ratio of 4.5:10, heat to 85°C, and stir until a uniform emulsion forms. Add water to adjust the viscosity to an appropriate 50 mPa·s and solids content to 35% to 40%, resulting in a nonionic copolymerized polypropylene wax emulsion with a particle size (Dv50) of 1 μm.

[0204] S12. Prepare coating slurry:

[0205] Nonionic copolymerized polypropylene wax emulsion, polymethyl methacrylate, boehmite, and water were mixed in a ratio of 28% organic particles: polyacrylonitrile: boehmite: water. All materials were added to a double planetary agitator and stirred for 3 hours at 30 rpm and 2000 rpm, with vacuum defoaming applied throughout the process. The coating slurry viscosity was controlled between 500 and 800 mPa·s (25°C). The boehmite particle size (Dv50) was 1 μm.

[0206] S2. Film formation treatment of coating slurry on the surface of base film:

[0207] The coating slurry in step S1 was coated on one side of a 7 μm PE base film to form a wet film, and then dried to form a 2 μm coating on one side of the PE base film; wherein the coating slurry coating speed was 80 m / min, the oven temperature was 65° C., and the total drying time was 3 min.

[0208] Example A2

[0209] This embodiment provides a separator and a method for preparing the same. The separator of this embodiment is identical to the separator of Example A1 except for the difference in the particle size of the polymer particles and the particle size of the inorganic particles contained in the coating.

[0210] Specifically, S11.b. mixed the intermediate product and nonionic emulsifier (fatty alcohol polyoxyethylene ether AEO-3) in a ratio of 4.5:5 and heated to 80°C. This produced a nonionic copolymerized polypropylene wax emulsion with a particle size Dv50 of 1.5 μm. The boehmite particle size Dv50 of S12 was also 1.5 μm.

[0211] Example A3

[0212] This embodiment provides a separator and a method for preparing the same. The separator of this embodiment is identical to the separator of embodiment A1 except for the polymer particles. Specifically, the polymer particles of this embodiment are low-melting-point polyamide.

[0213] Example A4

[0214] This embodiment provides a separator and a method for preparing the same. The separator of this embodiment and the separator of Example A1 have the same characteristics except for the particle size of the polymer particles, as shown in Table 1 below.

[0215] Example A5

[0216] This embodiment provides a separator and a method for preparing the same. The separator in this embodiment is identical to the separator in Example A1, except that the coating does not contain inorganic particles. The coating slurry components are mixed in a ratio of 45% polymer particles: 25% polymethyl methacrylate: 0% boehmite: 30% water.

[0217] Comparative Example A1

[0218] This comparative example provides a separator, which is different from the separator in Example A1 in that the separator coating does not contain polymer particles. The remaining features are identical.

[0219] The diaphragm preparation method of this comparative example refers to the diaphragm preparation method of Example A1. The difference from the preparation method of Example A1 is that when preparing the coating slurry, the coating slurry components are mixed in a ratio of organic particles: polymethyl methacrylate: boehmite: water = 0%: 22%: 43%: 35%. The steps and process conditions are the same.

[0220] Comparative Example A2

[0221] This embodiment provides a separator and a method for preparing the same. The separator of this embodiment is identical to the separator of Example A1 except for the different particle sizes of the polymer particles contained in the coating.

[0222] Specifically, S11.b. The intermediate product and nonionic emulsifier (fatty alcohol polyoxyethylene ether AEO-3) are mixed in a ratio of 4.5:10 and heated to 90° C. to obtain a nonionic copolymerized polypropylene wax emulsion with a particle size Dv50 of 0.9 μm.

[0223] Comparative Example A3

[0224] This embodiment provides a separator and a method for preparing the same. The separator of this embodiment is identical to the separator of Example A1 except for the difference in the particle size of the polymer particles and the particle size of the inorganic particles contained in the coating.

[0225] Specifically, S11.b. mixed the intermediate product and nonionic emulsifier (fatty alcohol polyoxyethylene ether AEO-3) in a ratio of 4.5:5 and heated to 75°C. This produced a nonionic copolymerized polypropylene wax emulsion with a particle size Dv50 of 1.6 μm. The boehmite particle size Dv50 of S12 was 1.5 μm.

[0226] 2. Secondary Battery Cell Example

[0227] Example B1 to Example B5 and Comparative Examples B1 to Comparative Examples B3;

[0228] Embodiments B1 to B5 and Comparative Examples B1 to B3 each provide a secondary battery cell, each comprising a positive electrode, a separator, and a negative electrode forming a battery cell, and also comprising an electrolyte. The separators provided in Embodiments A1 to A5 and Comparative Examples A1 to A3 are the separators provided in Embodiments B1 to B5 and Comparative Examples B1 to B3, respectively. The separator in Embodiment A1 serves as the separator in the battery cell of Embodiment B1, the separator in Embodiment A2 serves as the separator in the battery cell of Embodiment B2, and so on. The separator in Comparative Example A3 serves as the separator in the battery cell of Comparative Example B3.

[0229] The positive electrode was prepared as follows:

[0230] Using methyl pyrrolidone (NMP) as solvent, LiNi 0.8 Co 0.1 Mn 0.1 O2, carbon nanotubes (CNT), and binder (PVDF) are mixed in a mass ratio of 97:2:1 to prepare a cathode slurry with a solid content of 85%. The cathode slurry is evenly coated on aluminum foil, with a double-sided coating, where the surface density of each single side is 0.131g / 1540.25mm 2 After being fully dried, cold pressed and cut, the positive electrode sheet is obtained as the positive electrode.

[0231] Negative electrode: Using water as solvent, artificial graphite, conductive agent SP, dispersant (CMC), and binder (SBR) were mixed at a mass ratio of 96:1:1:2 to prepare a negative electrode slurry with a solid content of 58%. The positive electrode slurry was evenly coated on aluminum foil, with a double-sided coating of 0.065g / 1540.25mm on each side. 2 After being fully dried, cold pressed, and cut, the negative electrode sheet was obtained as the negative electrode. Electrolyte: At room temperature, ethylene carbonate (EC) and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1, and LiPF6 was added to the mixed solution to obtain a solution with a concentration of 1 mol / L as the electrolyte;

[0232] Secondary battery assembly: In a low-humidity constant temperature room, the positive and negative electrode sheets prepared as above are stacked and wound in the order of "positive electrode-separator-negative electrode" to form a bare cell, which is then filled with electrolyte to assemble into a lithium-ion secondary battery.

[0233] Performance tests of diaphragms and secondary battery cells

[0234] The separators and secondary battery cells provided in the above embodiments and comparative examples were tested respectively.

[0235] 1. Diaphragm performance test:

[0236] 1.1 The membranes in Examples A1 to A5 and Comparative Examples A1 to A3 were tested for the relevant properties listed in Table 1, including membrane absorption and infiltration diameter and air permeability. All test methods were in accordance with national standards (if no national standards were available, industry standard methods were used). For example, air permeability was tested using a membrane air permeability tester in accordance with the reference standard GB / T 36363-2018. Unless otherwise specified, the volume distribution particle size Dv50 of the organic particles in the examples of this application was determined using a particle size analyzer-laser diffraction method. Specifically, the measurement was performed using a laser diffraction scattering particle size analyzer (Mastersizer 3000 laser particle size analyzer) with reference to the standard GB / T 19077-2016, in accordance with the manufacturer's instructions.

[0237] The measured results are shown in Table 1 below.

[0238] Table 1

[0239]

[0240]

[0241] Table 1 shows that the air permeability of Comparative Example A1 at room temperature and after heating at 120°C for 15 minutes is essentially equivalent to that of Examples A1 to A5. This indicates that the separators of the present invention have good air permeability when the ambient temperature is below the melting point of the polymer particles contained in the coating. When the ambient temperature is above the melting point of the polymer particles contained in the coating, the polymer particles contained in the separator coating melt and seal the pores in the base membrane, causing the separator to lose its air permeability, thereby effectively preventing metal ion migration or positive-negative electrode crosstalk reactions within the battery.

[0242] Compared with Example A1, Example A5 has poor air permeability at room temperature and a slightly lower infiltration diameter. This indicates that adding inorganic particulate fillers is preferred because it can increase the porosity of the coating and improve air permeability.

[0243] Compared with Examples A1 to A4, the infiltration diameters of Comparative Examples A2 and A3 are poor. It can be seen that keeping the particle size Dv50 of the organic and inorganic particles consistent avoids the formation of continuous or discontinuous gradations, which can increase the pores between the particles and improve the liquid absorption and storage capacity.

[0244] 2. Secondary battery cell performance test:

[0245] 2.1 Secondary battery cell membrane air permeability after liquid injection

[0246] After the secondary battery cells in the above-mentioned Examples B1 to B5 and Comparative Examples B1 to B3 were injected and formed under the same injection and formation conditions, the batteries were disassembled to obtain each diaphragm, and the air permeability of each diaphragm was tested according to the diaphragm permeability method in Section 1.1 above. The measured results are shown in "After injection and high-temperature (85°C) aging" in Table 1.

[0247] Compared with Example B1, the air permeability of Example B4 after injection aging is poor, which shows that non-ionic group modification is preferred to help improve the pressure resistance of the polymer particles during battery use.

[0248] 2.2 Secondary battery cell cycle test

[0249] The secondary battery cells in the above-mentioned Examples B1 to B5 and Comparative Examples B1 to B3 were subjected to 0.33C discharge and 3C discharge tests, respectively, and the discharge capacity differences were expressed as percentages. The test results are shown in Table 2.

[0250] Table 2

[0251] Example 0.33C rate discharge 3C high rate discharge Example B1 100% 99% Example B2 100% 100% Example B3 100% 98% Example B4 95% 95% Example B5 98% 98% Comparative Example B1 100% 100% Comparative Example B2 100% 85% Comparative Example B3 100% 85%

[0252] As shown in Table 2, compared to Examples A1 to A3, Comparative Examples A2 and A3 have comparable 0.33C discharge capacities, but inferior 3C discharge capacities. This is because during charging, the anode expands, squeezing the electrolyte out of the cell. During discharge, if the electrolyte doesn't flow back in time, the discharge capacity is low. This phenomenon is exacerbated as the discharge rate increases. Therefore, the separator of the present invention, while not only reducing its air permeability at high temperatures, also improves its liquid absorption, ensuring high-rate discharge performance.

[0253] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some or all of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A diaphragm, characterized in that: The invention comprises a base film and a coating disposed on at least one surface of the base film, wherein the coating comprises organic particles, the organic particles comprise nonionic groups, and the volume distribution particle size D of the organic particles is v 50 is 1μm to 1.5μm.

2. The diaphragm according to claim 1, characterized in that The molar percentage of the nonionic groups in the organic particles is 0.1% to 5%, and can be 1% to 3%; and / or The nonionic group includes at least one of an ethoxy group, a hydroxyl group, and a carboxylate group.

3. The diaphragm according to claim 1 or 2, characterized in that: The material of the organic particles includes a polymer, and the weight average molecular weight of the polymer is 1000 to 10000, and can be 1500 to 8000; and / or The melting point of the organic particles is 95°C to 130°C, and optionally 95°C to 110°C; and / or The material of the organic particles contains a polymer, and the polymer includes at least one of polystyrene, polyethylene, polyimide, melamine resin, phenol resin, cellulose, cellulose modifier, polypropylene, polyester, polyphenylene sulfide, polyaramide, polyamideimide, polyimide, and a copolymer of butyl acrylate and ethyl methacrylate.

4. The diaphragm according to any one of claims 1 to 3, characterized in that: Based on the total dry weight of the coating as 100%, the content of the organic particles in the coating is ≥18wt%, and can be optionally 18wt% to 32wt%.

5. The diaphragm according to any one of claims 1 to 4, characterized in that: The coating also includes an inorganic particulate filler.

6. The diaphragm according to claim 5, characterized in that The inorganic particle filler satisfies at least one of the following conditions: (1) based on the total dry weight of the coating being 100%, the content of the inorganic particulate filler in the coating is 20 wt % to 28 wt %; (2) Volume distribution particle size D of the inorganic particle filler v 50: 1 μm to 1.5 μm; (3) The inorganic particle filler includes at least one of inorganic particles having a dielectric constant of 5 or more, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of undergoing electrochemical reactions.

7. The diaphragm according to any one of claims 1 to 6, characterized in that: The coating also includes an aqueous binder.

8. The diaphragm according to claim 7, characterized in that The content of the aqueous binder in the coating is 16 wt % to 28 wt % based on the total dry weight of the coating being 100 %; and / or The thermal decomposition temperature of the aqueous binder is ≥160°C, and can be selected from 160°C to 300°C.

9. The diaphragm according to any one of claims 1 to 8, characterized in that: The thickness of the base film is 4 μm to 7 μm; and / or The coating has a thickness of 2 μm to 5 μm; and / or The surface density of the coating is 2 g / m 2 Up to 8g / m 2 .

10. A method for preparing a diaphragm, characterized in that: The steps include: Provide a base film and a coating slurry containing organic particles; the organic material of the organic particles contains non-ionic groups, and the volume distribution particle size D of the organic particles v 50: 1 μm to 1.5 μm; The coating slurry is coated on at least one surface of the base film, and a coating is formed after drying to obtain a separator.

11. The preparation method according to claim 10, characterized in that: The coating slurry further comprises an inorganic particle filler and an aqueous binder; wherein the mass ratio of the organic polymer particles, the inorganic particle filler and the aqueous binder in the coating slurry is (18 to 32): (20 to 28): (16 to 28); and / or The solid content of the coating slurry is 30wt% to 40wt%; and / or The coating slurry has a viscosity of 100 mPa·s to 1000 mPa·s at 25°C.

12. The preparation method according to claim 11, characterized in that: The aqueous binder is added in the form of an aqueous binder aqueous solution, and the aqueous binder aqueous solution has at least one of the following conditions: The aqueous binder solution has a viscosity of 3000 mPa·s to 10000 mPa·s at 25° C.; The solid content of the aqueous binder solution is 40 wt % to 50 wt %.

13. The preparation method according to any one of claims 10 to 12, characterized in that: When the organic particles are polymer particles containing nonionic groups, the polymer particles are prepared by a method comprising the following steps: The polymer precursor particles, the ethoxy-containing polymer and the initiator are mixed and reacted to obtain polymer particles containing nonionic groups; The polymer particles containing nonionic groups are emulsified with a nonionic surfactant to obtain a nonionic polymer emulsion.

14. The preparation method according to claim 13, characterized in that: The polymer precursor particles, the ethoxy-containing polymer and the initiator are mixed in a ratio of (300 to 400): (90 to 125): (20 to 50); and / or The material of the polymer precursor particles includes at least one of polystyrene, polyolefin, polyimide, melamine resin, phenol resin, cellulose, polyester, polyphenylene sulfide, polyaramid, polyamideimide, and copolymer of butyl acrylate and ethyl methacrylate; and / or The ethoxy-containing polymer comprises at least one of allyl polyethylene glycol and bisallyl polyether; and / or The initiator comprises at least one of di-tert-butyl peroxide and dicumyl peroxide; and / or The reaction temperature is 130°C to 140°C; and / or The polymer particles and the nonionic surfactant are emulsified in a mass ratio of (4 to 6):

1.

15. The preparation method according to claim 13 or 14, characterized in that: The nonionic polymer emulsion satisfies at least any one of the following conditions (1) to (4): (1) The viscosity of the nonionic polymer emulsion at 25° C. is 10 mPa·s to 100 mPa·s; (2) The solid content of the nonionic polymer emulsion is 35wt% to 40wt%; (3) The pH value of the nonionic polymer emulsion is 5 to 6; (4) The nonionic surfactant includes a molecular structure of Wherein, R1 is a carbon chain alkyl group, R2 is a hydrophilic group, and n is a positive integer from 3 to 20.

16. The preparation method according to claim 15, characterized in that: The carbon chain alkyl is a long carbon chain alkyl of C12 to C18; and / or The R2 is at least one of a carboxyl group, an amine group, an aldehyde group, an alcohol group, an amino group, and an amide group.

17. The preparation method according to any one of claims 13 to 16, characterized in that: The nonionic surfactant includes at least one of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, castor oil polyoxyethylene ether, fatty amine polyoxyethylene ether, sorbitan fatty acid ester and polyoxyethylene sorbitan fatty acid ester.

18. The preparation method according to any one of claims 10 to 17, characterized in that: The coating slurry is applied at a rate of 50 m / min to 100 m / min; and / or The drying temperature is 60°C to 70°C; and / or The drying time is 1 min to 3 min.

19. A battery, characterized in that: The invention comprises a positive electrode, a negative electrode and a separator stacked between the positive electrode and the negative electrode, wherein the separator is the separator according to any one of claims 1 to 9 or the separator prepared by the preparation method according to any one of claims 10 to 18.

20. The battery according to claim 19, characterized in that The coating layer is disposed on one surface of the separator, and the coating layer faces the negative electrode.

21. An electrical device, characterized in that: The electrical device comprises the battery as claimed in claim 19 or 20, and the battery is used to provide electrical energy.

Citation Information

Cited By

  • High-temperature-resistant lithium ion battery diaphragm with high ionic conductivity and preparation method thereof

    CN120691046A